Influencia del clima organizacional en la satisfaccion laboral de los trabajadores de la empresa sunshine export s.a.c. tambogrande - piura en el año 2014 - Gutierrez Dávila, Junet Cristina (2014)
This type of investigation and explanation – applied, was held in the agribusiness Sunshine Export S.A.C – Tambo Grande – Piura, during the months of april to september, with the aim of determining the influence of organizational climate on job satisfaction of employees of the company. This research has shown 97 workers; emphasis was placed on identifying markers and motivation within the organizational environment; regarding job satisfaction was noted in commitment and self-realization. The present report is structured in the following way: The CHAPTER I: Makes mention of the problematic reality, history of study, theoretical, conceptual, problem, hypothesis and objectives. The CHAPTER II: methods, techniques and tools that were used to achieve the planned objectives, as well as population and sample that has worked is drawn. The CHAPTER III: This referred to the presentation of results and discussion. And finally he gives to know the conclusions, recommendations and bibliographic